Perfil empreendedor e performance dos microempreendedores individuais do curimataú oriental da paraíba - Moura, Heloísa Mirelli Diniz da Conceição (2022)
The objective of this work is to survey the profile of the Individual Microentrepreneur (MEI), a business category linked to the National Register of Legal Entities (CNPJ), created to formalize those who work on their own, sanctioned by the Brazilian government through Law 128, in addition to Law 123/2006, which came into force on December 19, 2008. For some, such public policy can serve as a tool for economic, human and social development based onthe “entrepreneurial spirit”; for others, just a marketing solution imposed by contemporary capitalism for the “enterprise” of the less favored population. Within this context, the objective of this work is to analyze the profile of Individual Microentrepreneurs from Curimataú Oriental da Paraíba through a quantitative research methodology, based on a bibliographical review and research aimed at the target audience, which addresses the peculiarity of each interviewee on how he behaves. sees in this challenging context of undertaking in Brazil. The literature review was developed through extensive research in books, academic databases and institutional sources that deal with entrepreneurship and small business, such as the Entrepreneur Portal (Federal Government - Companies and Business), SEBRAE Platforms and academic work platforms. Among the results obtained, it was possible to observe that in the profile of the MEI of Curimataú Oriental da Paraíba, the average age group of Microentrepreneurs is 25 to 39 years old, with 54% of them having completed higher education. In addition, 54.2% of entrepreneurs have an income of 1 to 5 minimum wages, and 58% feel fulfilled doing what they like as an MEI.